2003
DOI: 10.1002/qua.10640
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular proton transfer induced by divalent alkali earth metal cation in the gas state

Abstract: Interactions between divalent alkali earth metal (DAEM) ions M (MABe,Mg, Ca, Sr, Ba) and the second stable glycine conformer in the gas phase, which can transfer into the ground-state glycine-M 2ϩ (except the glycine-Be 2ϩ ) among each corresponding isomers when these divalent metal ions are bound, are studied at the hybrid three-parameter B3LYP level with three different basis sets. Proton transfers from the hydroxyl to the amino nitrogen of the glycine without energy barriers have been first observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…While it is well established that the zwitterionic form of glycine is not stable in the gas phase, preformed complexes in solution between metal ions and zwitterionic glycine may be directly transferred in the gas phase by ESI. Furthermore, many theoretical studies have shown that zwitterionic glycine can be strongly stabilized through the interaction with metal ions, so that this particular conformation, usually named salt bridge, is generally the global minimum and can play a key role in the unimolecular reactivity of M 2+ /glycine complexes …”
Section: Resultsmentioning
confidence: 99%
“…While it is well established that the zwitterionic form of glycine is not stable in the gas phase, preformed complexes in solution between metal ions and zwitterionic glycine may be directly transferred in the gas phase by ESI. Furthermore, many theoretical studies have shown that zwitterionic glycine can be strongly stabilized through the interaction with metal ions, so that this particular conformation, usually named salt bridge, is generally the global minimum and can play a key role in the unimolecular reactivity of M 2+ /glycine complexes …”
Section: Resultsmentioning
confidence: 99%
“…Due to the importance of information about the gas-phase intrinsic properties for the solution-phase measurements, 21 a number of attempts have been made at stabilizing and characterizing the gas-phase zwitterions. These efforts have concentrated on the hydrated, [22][23][24] or the metal-ion cationized zwitterionic systems, [25][26][27][28][29] etc. For the hydration of the zwitterionic glycine, Jensen et al 30 have determined that two water molecules can stabilize the glycine zwitterion.…”
Section: Introductionmentioning
confidence: 99%
“…For the hydration of the zwitterionic glycine, Jensen et al 30 have determined that two water molecules can stabilize the glycine zwitterion. Metal cationization can not only stabilize zwitterionic systems [25][26][27][28][29] but can also result in many biological functions. For example, the osmotic equilibrium of cells, the electrical excitability of nerves and muscles, the active transport of glucides and amino acids all involve the alkali metal cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BE of G 2 K1 + obtained by Wong et al [19] is 33.1 kcal/mol, in good agreement with our result. Similarly, the BEs of the charge-solvated GBe 2+ and GMg 2+ are about À300.3 and À170.8 kcal/mol [30], respectively, lower than their G 2 Be1 2+ (À315.4 kcal/mol) and G 2 Mg1 +/2+ (À185.8 kcal/mol) counterparts. Thus the extension of peptide chain between two cations is favorable to the binding of the metal-ion, which confirms, from another point of view, that extension of peptide chain can effectively decrease the electronic repulsive effect between two cations (H + and M +/2+ ) in the G 2 H + Mx +/2+ and weaken the positive BEs of the M-O bonds.…”
Section: Be Of the G 2 MX +/2+ /G 2 H + Mx +/2+mentioning
confidence: 91%